(untitled) (Ameghiniana, 2014)
The lithographic limestones of the Los Catutos Member (Vaca Muerta Formation, Neuquén Province, Argentina) (late middle– early late Tithonian) bear a great diversity of marine reptiles. These deposits are unique in the Southern Hemisphere as the record of lithographic limestones from the Upper Jurassic is restricted to the Northern Hemisphere, particularly to Western Europe. Some European basins are very close in age (late Kimmeridgian–early Tithonian) but they do not reach the middle–late Tithonian. Additionally, in the European basins the marine reptiles are mixed with continental biota whereas in Los Catutos Member the biota is exclusively marine, with the pterosaurs being the only exception. The strictly marine biota is composed by ichthyosaurs, two different species of turtles, one crocodyliform, and one plesiosaur. The taxonomic composition of Los Catutos Member is very similar to that found in Cerro Lotena (Portada Covunco Member, middle Tithonian) (Vaca Muerta Formation). These members share the same turtle species and one metriorhynchid genus, while ichthyosaurs only coincide at a family level. The study of marine reptiles from the Los Catutos Member, along with studies from other localities of the Neuquén Basin, have made an important contribution in filling the gaps in the evolutionary history of each of the represented clades. In this regard, they represent the only known marine reptiles from Gondwana throughout the Jurassic/Cretaceous transition, which is poorly represented in other regions of the world.